2015
DOI: 10.1515/bgeo-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of macro-scale circulation types on the occurrence of frosty days in Poland

Abstract: The research aimed at determining the variability of occurrence of frosty days in Poland and defining the impact of macro-scale circulation types on the occurrence of these days from December to March. The study used daily data on the minimum, maximum and mean daily air temperature for 15 stations located in Poland from 40 winter seasons between 1970/71 and 2009/10. During that period, a decrease in the number of frosty days was noticed across the greater part of Poland; still, these changes were not statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
8
0
4
Order By: Relevance
“…Numerous studies have shown that the increase in air temperature in winter observed over the recent decades has caused a decrease in the frequency of frosty days and cold spells (Tomczyk 2015;Lhotka and Kyselý 2015;Owczarek and Filipiak 2016). Considerably less attention has been paid to the winter occurrence of exceptionally warm periods, the effects of which concern both the natural environment and human life and economyparticularly the agricultural sector (Menzel et al 2011).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Numerous studies have shown that the increase in air temperature in winter observed over the recent decades has caused a decrease in the frequency of frosty days and cold spells (Tomczyk 2015;Lhotka and Kyselý 2015;Owczarek and Filipiak 2016). Considerably less attention has been paid to the winter occurrence of exceptionally warm periods, the effects of which concern both the natural environment and human life and economyparticularly the agricultural sector (Menzel et al 2011).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The impact of the North Atlantic Oscillation (NAO) on air temperature and atmospheric precipitation has been described in detail [8,28,40,[56][57][58], as a macroscopic pattern of atmospheric circulation that determines climatic conditions [59]. Regarding Poland, research into the NAO focuses on, for example, the occurrence of frosty days [60], snow cover [61,62], seasonal river run-off [63], and also water levels, thermal characteristics, and ice phenomena on lakes [64,65]. The influence of NAO variability on hydrological phenomena, including on the hydrological regime, changes in flow rate, and the thermal and ice regime of rivers and lakes, has been described, among others, by Yoo and D'Odorico [29] and Klavins et al [33].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in its intensity affect, among other things, the course of precipitation and air temperature [9,10]. Whereas in the case of NAO the relationships are relatively thoroughly investigated, in the case of other circulation patterns, such an approach still requires more detailed research [11,12]. In addition to the aforementioned circulation type, climatic conditions in Europe (with variable intensity) are affected by other circulation patterns, including the Arctic Oscillation (AO), East Atlantic pattern (EA), East Atlantic/Western Russia (EAWR), and the Scandinavian pattern (SCAND).…”
Section: Introductionmentioning
confidence: 99%